2021
DOI: 10.1039/d1nr03649a
|View full text |Cite
|
Sign up to set email alerts
|

High-performance triboelectric nanogenerators based on the organic semiconductor copper phthalocyanine

Abstract: In this work, we fabricated triboelectric nanogenerators (TENGs) with the triboelectric friction layer made of organic semiconductor copper phthalocyanine (CuPc). Iodine was incorporated into the CuPc to tune the work...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…(b) Magnified image from red dotted box of panel a. Data from refs , , , , , , , , , , , , and .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Magnified image from red dotted box of panel a. Data from refs , , , , , , , , , , , , and .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Nevertheless, friction materials treated by these methods tended to be less stable. In recent years, researchers found that semiconductors can also produce charge transfer by rubbing against another material and could generate direct current (DC) with high density, which gives them an advantage over conventional TENGs. Therefore, the triboelectrification phenomenon between semiconductors has been given more and more attention. It is noteworthy that the third-generation semiconductor materials (for instance, gallium nitride (GaN)) have the characteristics of large bandgap width, high breakdown field strength, and high electron saturation speed, which can achieve excellent output performance for nearly two years as a new friction materials. …”
Section: Introductionmentioning
confidence: 99%
“…However, though with highly negative charge storing capability, the practicality and popularity of these traditionally used dielectric frictional polymer materials are usually limited due to its inherent low current density output [19]. To address these challenges, the integration of semiconductors [20] with competitive electronic conductivity into TENGs becomes an outstanding approach for robust TENG formation. These schemes can facilitate charge transition thereby optimizing electrical output performances.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the above-mentioned properties, OSPs have been recognized as one of the most favourable materials for TENG applications. 33–35 Typical OSPs include polyaniline (PANI), 36 polypyrrole (PPy), 37 polyacetylene (PA), 38 poly(phenylenevinylene) (PPV), 39 (PEDOT: PSS) 40 etc. A number of studies have been carried out on the use of the above mentioned OSPs for TENGs.…”
Section: Introductionmentioning
confidence: 99%